Pembelajaran IPS untuk Menumbuhkan Kesadaran Multikultural pada Siswa SMP Negeri 2 Tantom Angkola - Rusydah, Imro Atur; Saragih, Ridho Gilang Amalsyah (Medan Resource Center, 2025)
This study aims to explore the role of Social Studies (IPS) education in instilling multicultural values in students at SMP Negeri 2 Tantom Angkola. This research adopts a qualitative approach with literature study and interviews conducted with students and IPS teachers at SMP Negeri 2 Tantom Angkola. The findings of the study indicate that IPS education has great potential to introduce and develop multicultural values, such as tolerance, respect for diversity, and cultural mutual respect. However, the implementation of these values in the classroom faces various challenges, including limited teaching materials and a lack of understanding among teachers regarding the importance of multicultural education. Therefore, strengthening the curriculum and providing training for educators is necessary to maximize the role of IPS education in fostering an inclusive and multicultural society